Does higher demand for medicinal plants lead to more harvest? Evidence from the dual trade of Nardostachy jatamansi and Fritillaria cirrhosa and Tibetan people’s harvesting behavior - Zhao, Jingjing; Hu, Sifan; Fan, Linyu; Zeng, Yan; Yang, Yongchuan; Zhao, Yao; Lee, Tien Ming (Frontiers in Ecology and Evolution, 2023)
Introduction As the demand for herbal medicines is surging worldwide, regions of medicinal plants are vulnerable to large-scale and unsustainable exploitation for commercial trade and use. Yet, we still lack the understanding about the relationship between indigenous people harvesting and trade practices of medicinal plants and their influencing factors for possible intervention measures. Methods Here, we combined qualitative and quantitative methods to survey traders (N = 20) and local harvesters (N = 923) from nine Tibetan townships in Hongyuan county, Sichuan Province, on the eastern Qinghai-Tibetan plateau in China. Specifically, we elucidated the local value chain of medicinal plants trade and harvest of Nardostachy jatamansi and Fritillaria cirrhosa, and explored the factors influencing harvester’s willingness to harvest these plants. Furthermore, we empirically tested the constructs of the COM-B model (Capability, Opportunity, Motivation -Behavior) in predicting the sustainable harvesting behavior of medicinal plants. Results and Discussion Our results revealed that the trade characteristics of N. jatamansi and F. cirrhosa were contrasting, and the sustainability of the former species was largely dependent on the latter one. Importantly, the traders’ practices were affected by the supply, while the harvesters’ willingness to harvest were mainly influenced by harvest incomes, past harvesting experience, and grassland tenure. Finally, though motivation was not directly affecting harvesting behavior, the harvesters’ ecological worldview indirectly affected their harvesting behavior, particularly through the mediation of the level of compliance of village rules and customs. Overall, our results provided crucial insights for the conservation and sustainable management of the valuable wild medicinal plants.